2017
DOI: 10.1002/cite.201700042
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Porous Silica Materials with Water at Ambient Conditions. Calculating the Pore Size Distribution from the Excess Surface Work Disjoining Pressure Model

Abstract: Characterization of mesoporous materials today is routinely performed recording the adsorption isotherm of nitrogen at 77 K. The pore size distribution (PSD) can subsequently be determined using either thermodynamics or statistical mechanics based approaches. While nitrogen has evolved as the reference adsorptive, other gases are often used to extract more information from the isotherm. This contribution is focused on the calculation of a PSD from the water vapor isotherm. It is demonstrated that water adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…This is an advantage, given that in terms of ice nucleation ability we are interested in the interaction of soot particles with water vapor. Besides, recent studies have shown that PSD derived from water sorption reveals comparable results to other methods frequently used (Georgi et al, 2017). Finally, we would like to point out the limitations of the method to derive a PSD.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 80%
See 3 more Smart Citations
“…This is an advantage, given that in terms of ice nucleation ability we are interested in the interaction of soot particles with water vapor. Besides, recent studies have shown that PSD derived from water sorption reveals comparable results to other methods frequently used (Georgi et al, 2017). Finally, we would like to point out the limitations of the method to derive a PSD.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 80%
“…When studying porous silica particles, n c is often assumed to be equivalent to an adsorbed water monolayer capacity (e.g., Adolphs & Setzer, ; Adolphs, ). Using this monolayer capacity, the film thickness can be calculated at any amount of water adsorbed by t=nancΔGaτ, where τ is the thickness of a single layer of adsorbate ( τH2O=0.24 nm; Georgi et al., ). What remains to be done is a transformation of the sorption isotherms from V a − p / p 0 coordinates into V a ‐ r coordinates, in order to derive an expression for the dV a / dr term when evaluating equation .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17] However, other gases have also been used, for instance argon and hydrogen 14 as well as the water vapor. 18 The cases of equal and different PSDs obtained by different probes were reported; 16 the differences could be particularly due to inter-pore connectivity, which might appear different for different probes.…”
mentioning
confidence: 98%